2022
DOI: 10.3847/1538-4365/ac721a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Radiative Parameters of Highly Excited Odd-parity Levels in Ir ii

Abstract: Using the time-resolved laser-induced fluorescence technique, the radiative lifetimes for 15 odd-parity levels from 47,003 to 61,475 cm−1 in Ir ii were measured. To the best of our knowledge, 11 lifetime results among these levels are reported for the first time, and hence they should be a good complement to the measured lifetime data of 10 levels previously published in the literature. The pseudorelativistic Hartree–Fock including core-polarization corrections method was used to calculate the lifetimes and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Besides, since the cutoff radius is not an unambiguously defined parameter, Gamrath et al [45] determined that another definition of the core radius corresponding to a value 33% smaller only affects the computed radiative lifetimes by a few percents in the case of neutral lanthanum (La I). As previously observed in other weakly charged ions (e.g., [37,38]), CPOL effects reduce the f -values for both U II and U III by up to 10-15% in both cases. The direct consequence on the opacities can be observed when looking at Figs.…”
Section: Opacity Sensitivity To Core-polarization Effectssupporting
confidence: 84%
See 1 more Smart Citation
“…Besides, since the cutoff radius is not an unambiguously defined parameter, Gamrath et al [45] determined that another definition of the core radius corresponding to a value 33% smaller only affects the computed radiative lifetimes by a few percents in the case of neutral lanthanum (La I). As previously observed in other weakly charged ions (e.g., [37,38]), CPOL effects reduce the f -values for both U II and U III by up to 10-15% in both cases. The direct consequence on the opacities can be observed when looking at Figs.…”
Section: Opacity Sensitivity To Core-polarization Effectssupporting
confidence: 84%
“…The latter can be approximately represented by a core polarization (CPOL) model potential, first introduced in HFR and described in details in [29]. It was shown that considering CPOL effects in HFR calculations can reduce the predicted oscillator strengths in some cases (e.g., [37,38]). The CPOL potential essentially depends on two parameters: the dipole polarizability of the ionic core, α d , and its cutoff radius, r c , often estimated as the outermost core orbital mean radius.…”
Section: Opacity Sensitivity To Core-polarization Effectsmentioning
confidence: 99%